2018
DOI: 10.1002/adfm.201800179
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasensitive Photoresponsive Devices Based on Graphene/BiI3 van der Waals Epitaxial Heterostructures

Abstract: In recent years, bismuth iodide (BiI 3 ), a layered metal halide semiconducting light absorber with a wide bandgap of ≈1.8 eV and strong optical absorption in the visible region, has received greater attention for photovoltaic applications. In this study, ultrasensitive visible-light photodetectors with graphene/ BiI 3 vertical heterostructures are achieved by van der Waals epitaxies. The BiI 3 films deposited on graphene show flatter morphologies and significantly better crystallinities than that of BiI 3 fil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 48 publications
(38 citation statements)
references
References 81 publications
(122 reference statements)
0
37
0
1
Order By: Relevance
“…Group V-VI compounds (Sb, Bi/S, Se, Te) [33][34][35][36] and Group V-VII compounds (As, Sb, Bi/Cl, Br, I) of the nanowires have been investigated in photovoltaic materials [37] and they could be synthesized by chemical vapor transport (CVT) or chemical vapor deposition (CVD). Comparable photoresponse of WSe 2 /BiI 3 [38] and graphene/BiI 3 [39] van der Waals heterostructures have been demonstrated. Previous theoretical studies showed that group V trihalides had suitable bandgap, tunable bandedge and moderated mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Group V-VI compounds (Sb, Bi/S, Se, Te) [33][34][35][36] and Group V-VII compounds (As, Sb, Bi/Cl, Br, I) of the nanowires have been investigated in photovoltaic materials [37] and they could be synthesized by chemical vapor transport (CVT) or chemical vapor deposition (CVD). Comparable photoresponse of WSe 2 /BiI 3 [38] and graphene/BiI 3 [39] van der Waals heterostructures have been demonstrated. Previous theoretical studies showed that group V trihalides had suitable bandgap, tunable bandedge and moderated mobility.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to the case of BiI 3 on the graphene/SiO 2 substrate, for the Si and graphene/copper substrates, four peaks were located at 13.12°, 26.05°, 39.33°, and 53.19°, corresponding to the (00l) family planes of the BiI 3 structure. [38] However, the XRD peaks of BiI 3 on the graphene/copper substrate were obviously much higher than those of BiI 3 on the bare silicon substrate. [38] This could be because the BiI 3 crystals were well-orientated to the c-axis, thereby resulting in a much higher diffraction intensity of X-rays.…”
Section: Resultsmentioning
confidence: 91%
“…[38] However, the XRD peaks of BiI 3 on the graphene/copper substrate were obviously much higher than those of BiI 3 on the bare silicon substrate. [38] This could be because the BiI 3 crystals were well-orientated to the c-axis, thereby resulting in a much higher diffraction intensity of X-rays. This is consistent with the SEM results.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Because of numerous potential applications and diverse novel characteristics, much attention is currently given to fabricating and classifying nanomaterials with various morphologies [1]. In the past, nanomaterials of many shapes have been designed for various types of photoresponsive devices [2][3][4][5]. Nanomaterials, particularly one-dimensional nanostructures, have novel features and a wide-ranging scope for nano-device fabrication [6,7].…”
Section: Introductionmentioning
confidence: 99%